Perceptions Passengers on Service Quality: Public Transport in Kuala Lumpur - Imhimmed Mohamed Irtema, Hamza; Ismail, Amiruddin; Nazri Borhan, Muhamad; M Abdelsalam, Hassan.; B.Z Alshetwi, Abdurauf.; Ismael Albrka, Shaban; Milad, Abdalrhman; Mohashhash, Buseif; Y. Y. Alfakhri, Aboubaker; Muhammad Das, Amsori; A.M. Yahia, Hussin; Musbah Al Allam, Allam (International Journal of Engineering and Technology, 2018)
The quality of service is a measurement of the level of service provided against the expectations of customers. This research examines the behaviour of passengers using public transport with respect to the service quality of public transit. A questionnaire was answered by 412 passengers at one of the main railway stations, Kuala Lumpur Sentral. Empirical data were extracted based on the information collected from the survey. Structural equation modelling was used to examine the measurement model. The findings of the study reveal that public transport passengers are significantly influenced by service attributes, for example, vehicle safety, cleanliness of the facility, and management of complaints. These findings identify the important service attributes that public transportation services in Kuala Lumpur need to prioritise. This study will help ascertain whether service quality meets or exceeds the expectations of the passengers. Â